A Review of the Valid Methodological Use of Adaptive Comparative Judgment in Technology Education Research - Buckley, Jeffrey; Seery, Niall; Kimbell, Richard (Frontiers in Education, 2022)
There is a continuing rise in studies examining the impact that adaptive comparative judgement (ACJ) can have on practice in technology education. This appears to stem from ACJ being seen to offer a solution to the difficulties faced in the assessment of designerly activity which is prominent in contemporary technology education internationally. Central research questions to date have focused on whether ACJ was feasible, reliable, and offered broad educational merit. With exploratory evidence indicating this to be the case, there is now a need to progress this research agenda in a more systematic fashion. To support this, a critical review of how ACJ has been used and studied in prior work was conducted. The findings are presented thematically and suggest the existence of internal validity threats in prior research, the need for a theoretical framework and the consideration of falsifiability, and the need to justify and make transparent methodological and analytical procedures. Research questions now of pertinent importance are presented, and it is envisioned that the observations made through this review will support the design of future inquiry.